Public university and critical thinking in Brasil - Martins, Paulo Henrique (Revista de Ciências Sociais, 2019)
Sociology has an important role to rethink the academic and public strategies of redefining paradigms insofar as it can simultaneously articulate micro and macrossociological perspectives on institutional, theoretical and political issues. This paper aims to discuss the role of the public university for a humanistic knowledge in the social sciences and its relation with the private university. The rescue of a pioneering initiative that has been developed in the UFC, the College of Advanced Studies, should be remembered as an exemplary initiative because it points to the importance of articulating a complex and interdisciplinary thinking that is essential to rethink the public university.